Between The Local and the Global South: Diaspora’s Politics for the Recognition of the Armenian Genocide in Argentina 1965-2015 - Juan Pablo Artinian (International Journal of Armenian Genocide Studies, 2022)
Historiography has analyzed the recognition of the Armenian genocide using cultural and geopolitical coordinates belonging to both Western and Non-Western societies. However, the North-South dimension of this event and its effect on the diaspora has been neglected by most of the approaches taken by Armenian studies. In this article, I will analyze how the Armenian diaspora in Argentina advocated for recognition of the Armenian genocide from 1965 to 2015. This community is not only significant in terms of population – it is the largest in the Global South – but also because its contribution to the struggle for remembrance and recognition of the Armenian genocide is unique. Argentina is one of the few countries in which the genocide has been recognized by the executive, legislative, and judicial branches of government. In this article, I will analyze the specific dynamics of the Armenian-Argentine community’s local activism and its contribution to the global recognition of the genocide.1 The commemoration on April 24 in the official Argentine calendar, the recognition of the extermination of Armenians as genocide by Francis I, Roman Catholicism’s first Argentinean Pope, demonstrate the importance of the interaction between the local and global.